Nutritional requirement of newly isolated wild strain acetobacter tropicalis for the improvement of acetic acid production - Selvanathan, Yashini K; Nor Hasmaliana, Abdul Manas; Ikwebe, Joseph; Nasratun, Masngut (Semarak Ilmu Publishing, 2025)
The aim of this study was to determine the best nutritional requirements, focusing on sugar concentration and nitrogen sources, for a newly acetic acid strain Acetobacter tropicalisisolated from MD2 pineapple peels. To this aim, the identification of isolated strains from spontaneous fermentation of pineapple peel was done through PCR amplification and sequencing of the 16S rRNA gene. Identified Acetobacter tropicalisshows characteristics and biochemical traits align with Acetobactergenus. The study delves into the carbon and nitrogen source requirements for MD2 pineapple peel juice with varying sugar concentrations. The study explores how acidity, yield, and microbial growth are affected, uncovering optimal outcomes with particular sugar concentrations and levels of nitrogen sources. Notably, the addition of 0.25 g/L yeast extract resulted in the highest acidity of 36.03 g/L and product yield of 0.643 g acid/ g substrate and 0.011 g acid/ g biomass. Surprisingly, this new strain flourishes without a need of additional sugar. The findings contribute valuable information for optimizing acetic acid fermentation processes utilizing Acetobacter tropicalis, highlighting the importance of carbon and nitrogen sources for this strain.